Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4898732
|View full text |Cite
|
Sign up to set email alerts
|

Thermoconvective vortices in a cylindrical annulus with varying inner radius

Abstract: This paper shows the influence of the inner radius on the stability and intensity of vertical vortices, qualitatively similar to dust devils and cyclones, generated in a cylindrical annulus non-homogeneously heated from below. Little relation is found between the intensity of the vortex and the magnitude of the inner radius. Strong stable vortices can be found for both small and large values of the inner radius. The Rankine combined vortex structure, that characterizes the tangential velocity in dust devils, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The role of frictional dissipation in preventing the RMW from collapsing is also confirmed by Castaño et al . (). In contrast, Wang and Wang () attributed the non‐contracting RMW structure during the RI of Typhoon Megi (2010) to the rapid release of latent heat in the outer spiral rain bands interacting with a low‐level synoptic depression in which the storm was embedded.…”
Section: Introductionmentioning
confidence: 99%
“…The role of frictional dissipation in preventing the RMW from collapsing is also confirmed by Castaño et al . (). In contrast, Wang and Wang () attributed the non‐contracting RMW structure during the RI of Typhoon Megi (2010) to the rapid release of latent heat in the outer spiral rain bands interacting with a low‐level synoptic depression in which the storm was embedded.…”
Section: Introductionmentioning
confidence: 99%
“…We have observed that the double circulation appears, when the primary vortex destabilizes [11], only forā < 0.5. Whenā ≥ 0.5 the bifurcation does not lead to a subvortex.…”
Section: Secondary Whirlmentioning
confidence: 94%
“…A vertical vortex is formed. The behavior of the particles in the vortex is a spiral up motion around the inner cylinder [10,11]. As R continues increasing in the range of stability of the vortex, the azimuthal velocity component u φ grows, the vortex intensifies, as shown in Fig.…”
Section: Thermoconvective Bifurcation Diagrammentioning
confidence: 94%
See 2 more Smart Citations